Optimasi Teknik MRI untuk Knee Joint: Perbandingan PD TSE Fat Saturation dan T2 Fat Saturation BLADE pada Potongan Coronal - W.R.I, Muhammad Fajar; Prastanti, Agustina Dwi; Jannah, Marichatul (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: The use of PD TSE fat saturation (FS) sequences in coronal section of the MRI knee joint routine examination revealed artifacts caused by popliteal artery pulses. Meanwhile, there is T2 FS sequence with the BLADE technique that can reduce motion artifacts, but isn't used in the knee joint routine MRI examinations. BLADE is a technique of filling radial k-space around the center of k-space, thereby reducing motion artifacts and improving image quality. The aim of this study is to determine the differences in anatomical information, artifacts, and sequences that optimally reveal the anatomical information of knee joint between the PD TSE FS and T2 FS BLADE coronal section.Methods: This study used a quantitative research methods with an experimental approach. The sample of this study are 10 healthy volunteers and 2 radiologists as respondents. Each volunteer undergo an MRI knee joint examination with the PD TSE FS and T2 FS BLADE coronal section. The results of the two sequence images were assessed by the two respondents to obtain data for assessing anatomical information on the ACL, PCL, collateral ligament, articular cartilage, meniscus, subchondral bone, and artifact information. Data that has been obtained is processed using the Wilcoxon test.Results: The results shows that there are differences in the anatomical information of ACL, PCL, articular cartilage, and meniscus between the PD TSE FS and T2 FS BLADE coronal section. Meanwhile, there is no difference in the anatomy of the collateral ligament and subchondral bone. There is also a difference in artifact information between the two sequences.Conclusions: The T2 FS BLADE sequence is more optimal than the PD TSE FS sequence in displaying anatomic information and is also more optimal in suppressing ghosting artifacts from the popliteal artery pulse.